From Economic Remittances to Societal Transmittances Experiences form the European Union - Pries, Ludger (Contemporary Southeastern Europe, 2023)
Analysis and debates on remittances concentrate on sending money from the Global North to the Global South. Here we deepen the aspects of social remittances and propose a broader view on transmittances as bi-directional and multi-dimensional flows in the context of migration taking Europe as a region less taken into account in these debates. The effects of remittances have to be analyzed in the overall context of historical conditions, economic and demographic cycles and transnational societal textures between the regions under consideration. We take the example of the accession of Poland and of Romania and Bulgaria to the EU and show the usefulness of an extended perspective on transmittances, that is, taking into account the multifaceted bidirectional impacts of migration. Some conclusions on desiderata for further research are drawn.